CARACTERIZACION DE OBSIDIANAS ARQUEOLÓGICAS PERUANAS: REDES DE INTERCAMBIO - Rojas Ayala, Chachi (2004)
This work presents the results of the analysis done on obsidians samples that belong to three archeological collections at the Museum of Archeology and Anthropology of San Marcos University (MacNeish's collection, • dated toan age 8000- 3500 b. C.) and the I.N.C. Regional Museum at lea (Maymi and Casa Vieja collections, corresponding to the Middle Horizon period 800 a. D.). Additionaly, with the idea ofundertaking future work on the establishment of trade routes and provenience studies in Andean populations, sorne obsidian samples from volcanic sources near to the gathering points are studied. 57Fe Mossbauer spectroscopy (MS), X Ray Fluorescence, Proton Induced X- Ray Emission Spectroscopy (PIXE), Inductively Coupled Plasma-Atomic Emission Spectroscopy (ICP-AES) and Inductively Coupled Plasma-Mass Spectroscopy (ICP-MS) were used to analysis. MS study provides the cation ratio Fe2+/Fe3, based on infonnation coming from the local environment of iron atoms inside the vitreous structure of the obsidian, and also a set of hyperfine parameters for each one of the analyzed samples for comparative analysis. Starting from multielement chemical techníques such as ICP, PIXE and X ray fluorescence, variations in elemental composition are found among the samples studied.